Digital Marketing Strategy Training for Branding & Revenue UMKM Al-Qur'an Ma'sum Publisher - Susilaningdyah Mustikawati; Sayekti Endah Retno Meilani; Rina Trisnawati (Abdi Psikonomi, 2025)
The advancement of digital technology offers MSMEs opportunities to expand through digital marketing. However, many struggle with platform use, content creation, and strategy management. This program provides training and technical assistance for MSMEs at Penerbit Al-Qur’an Ma’sum, covering social media, marketplaces, SEO, Google Ads, WhatsApp Business, and Canva. Using a participatory approach, activities include awareness sessions, training, mentoring, and evaluation. The program enhances digital marketing skills, boosting business interactions and sales. Sustainability is ensured through post-training consultations and a digital community.